The Influence of Authentic Leadership And Psychological Capital on Work Engagement: The Mediating Role of Job Satisfaction - Della Nur Fadilah; Hermin Endratno (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the effects of Authentic Leadership and psychological capital on Work Engagement, with job jatisfaction serving as a mediating variable among healthcare workers at Indramayu Regional General Hospital, Indonesia. The study addresses inconsistent findings in previous research regarding the relationship between these variables, particularly in healthcare settings. A quantitative study employing a cross-sectional survey design was conducted. Data were collected through an online questionnaire from 100 healthcare workers selected using purposive sampling from a population of 478 employees. The data were analysed using partial Least Squares Structural Equation Modelling (PLS-SEM) with Smart PLS 4. The findings reveal that Authentic Leadership has no Signifficant effect on either Job Satisfaction or Work Engagement, and Job Satisfaction does not mediate the relationship between Authentic Leadership and Work Engagement. In contrast, Psychological has positive and Signifficant effect on both Job Satisfaction and Work Engagement. In additional, Job Satisfaction positively influences Work Engagement. These findings indicate that Psychological Capital is a stronger predictor of Work Engagement than Authentic Leadership among healthcare workers. The study extends the Job Demands Resources (JD-R) theory by highlighting Psychological Capital as an important personal resource that enhances Work Engagement through Job Satisfaction. Practically, hospital management should prioritise strategies that strengthen employees Psychlogical Capital and improve Job Satisfaction to foster higher Work Engagement better healthcare service quality.